Impact of substitute players on attacking technical performance: a case study of Johor Darul Ta'zim in the AFC Champions League Elite 2024/2025 - Sahira, Aliah; Mohd Zamri, Muhamad Akasyah; Mohamed, Muhamad Noor; Saiful Annur, Muhamad Safiq; Raja Hussain, Raja Nurul Jannat; Mazaulan, Mardiana; Md. Radzi, Noor Azila Azreen (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study evaluates the influence of substitute players on the attacking technical performance of Johor Darul Ta’zim (JDT) during the 2024/2025 AFC Champions League Elite. By analyzing key indicators such as passes, crosses, shots, and goals across eight matches via hand notational analysis, the research compares full-match players, substitutes, and substituted players using one-way ANOVA. The findings aim to identify variations in offensive output between these groups, providing evidence-based insights to optimize tactical substitutions and player deployment strategies in elite-level continental football.